Franz Xaver Wolfgang Mozart w lwowskim dyskursie muzykologicznym: aspekt historiograficzny i wykonawczy - Hawaluk, Roksolana (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
The patriarch of the musicological search of F. X. W. Mozart’s life and work in Galicia is the professor of the National Music Academy named after M. Lysenko in Lviv Dmytro Kolbin. His search, which began in the 1960s, served as the basis for the formation of the main milestones of his creative path, the determination of locations, components of creative work, the preparation of publications and concert performances. A new stage was the initiation of the Mozart Society in Lviv, which united a number of leading Lviv musicologists and performers, the establishment of the international classical music festival LvivMozArt, the implementation of the regional studies cluster program „Galicia – (un)explored land / Galicia – terra (in)cognita” and the publication of an annotated and the illustrated collection of documents „Mozart-son. The life of Franz Xaver in a travel diary and letters”. Formation of a powerful corpus of multi-vector musicological searches, concert and performance traditions that are able to introduce new accents and even a radical reconsideration of a number of events, creative contacts, inspirations of creative activity.